The necessity of theater : the art of watching and being watched - Woodruff, Paul, 1943- (Oxford : Oxford University Press, 2008)
What is unique and essential about theatre? What separates it from other arts? Do we need 'theatre' in some fundamental way? This text analyzes the unique power of theatre by separating it into the twin arts of watching and being watched, practised together in harmony by watchers and the watched.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Theater -- Philosophy; Gaze; Theater -- Psychological aspects